Engineering Lineage Potency and Plasticity of Stem Cells using Epigenetic Molecules. Issue 1 (December 2018) - Dhaliwal, Anandika; Pelka, Sandra; Gray, David; Moghe, Prabhas
Abstract Stem cells are considered as a multipotent regenerative source for diseased and dysfunctional tissues. Despite the promise of stem cells, the inherent capacity of stem cells to convert to tissue-specific lineages can present a major challenge to the use of stem cells for regenerative medicine. We hypothesized that epigenetic regulating molecules can modulate the stem cell's developmental program, and thus potentially overcome the limited lineage differentiation that human stem cells exhibit based on the source and processing of stem cells. In this study, we screened a library of 84 small molecule pharmacological agents indicated in nucleosomal modification and identified a sub-set of specific molecules that influenced osteogenesis in human mesenchymal stem cells (hMSCs) while maintaining cell viabilityin-vitro . Pre-treatment with five candidate hits, Gemcitabine, Decitabine, I-CBP112, Chidamide, andSIRT1/ 2inhibitor IV, maximally enhanced osteogenesisin-vitro . In contrast, five distinct molecules, 4-Iodo-SAHA, Scriptaid, AGK2, CI-amidine andDelphidine Chloride maximally inhibited osteogenesis. We then tested the role of these molecules on hMSCs derived from aged human donors and report that small epigenetic molecules, namelyGemcitabine and Chidamide, can significantly promote osteogenic differentiation by 5.9- and 2.3-fold, respectively. Taken together, this study demonstrates new applications of identified small molecule drugs for sensitively regulating the lineage plasticity fates of bone-marrow derived mesenchymal stem cells through modulating the epigenetic profile of the cells.